The Tyranny of Geography. - Grier, David Alan (Computer (00189162), 2015)
The software industry is more regional than one would think; most jobs in the field are centered in nine US cities. The Web extra at http://youtu.be/zlG75-adjcA is an audio recording of author David Alan Grier expanding on his Errant Hashtag column, in which he discusses how location plays an important role in software development and how nine cities hold 40 percent of the US software market, with particular specialties clustered in specific areas.